(-26 +46-100) - (-48+50) + (-49 +65)
5-[-2-(-1+5-6)-7]-3
[-10 +4] + [-3 +(7-5)] +(2-1)
-9-[-3-(1+2-3)] -3-(2+5)]
Respuestas
Respuesta dada por:
3
Respuesta:
-63 9 24 -16
Explicación:
(-26 +46-100) - (-48+50) + (-49 +65) =(-80)-(2)+(19)= -63
5-[-2-(-1+5-6)-7]-3 = 5-[-2-(-2)-7]-3= 5-(-7)-3= 9
[-10 +4] + [-3 +(7-5)] +(2-1) = -6+ [-3 +12]+21= -6+9+21=24
-9-[-3-(1+2-3)] -3-(2+5)]= -9-[-3] -3-(2+5)]=-6-3-7= -16
Preguntas similares
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años